Measuring the efficiency of light-emitting diode and high-pressure sodium vapour road lighting for penang bridge highway using the data envelopment analysis / Nina Sakinah Ahmad Rofaie - Nina Sakinah , Ahmad Rofaie (2023)
Road lightings are essential to ensure the safety and comfort of its users, especially to prevent accidents and assist visual tasks. The monumental shift from conventional road lighting technology to light-emitting diode (LED) lighting is happening in recent years. This shift is driven by energy efficiency, associated cost savings, and environmental concerns resulting from the road lighting system. Although Malaysia has been using LED for road lighting illumination since 2012, the earlier studies did not favor this adoption. Hence, there is a need to revisit the feasibility of LED for road illumination based on the current development like the reduction in the price of LED lights, raise in the price of energy, and the increased awareness in environmental concerns. This study aims to investigate the performance of LED in substitution for high-pressure sodium vapour (HPSV) road lighting in Penang Bridge using the Data Envelopment Analysis (DEA) approach by modeling energy, cost, and environment together. The first DEA model of Charnes, Cooper, and Rhodes (CCR) is used to investigate the technical efficiency of HPSV and LED road lightings by considering desirable output only. The second DEA Directional Distance Function (DDF) model examined the eco-efficiency of HPSV and LED road lightings by considering both desirable and undesirable outputs together. The third Bootstrap DEA (BDEA) model explored the bias-corrected efficiency of HPSV and LED road lightings for errors and confidence intervals assessment. Penang Bridge highway is chosen as the study area because the lantern retrofit is done on site without changing the other road lighting parameters such as the number and height of road lighting, the distance covered, spacing and arrangement of the lanterns. The decision making units (DMUs) is the metering point along the Penang Bridge, on which there are five units for each type of lighting technology. The selected input variables are the installation cost, operation cost, and energy consumption. The desirable output variables are the lifetime of lantern while the undesirable output is carbon dioxide (CO2) emissions from lighting usage. Based on the CCR model, the results show there is only one 100% technically efficient DMU (LED4) and the inefficiency scores range from 14.11 % to 83.76%. The mean performance for LED technology (66.31%) is two times higher than HPSV (37.38%) road lighting, reflecting the efficiency of road lighting on the Penang Bridge highway is much improved with LED adoption. Also, the evaluation of virtual input weights indicates installation cost as the most important variable in evaluating the performance of road lighting technology for this study. Findings from the DDF analysis further reveal two eco-efficient DMUs (LED4 and HPSV4), nonetheless, the average DDF eco-efficient scores of LED road lighting technology (74.77%) exceeds the HPSV road lighting (40.06%). The analysis of BDEA model show the mean performance of LED road lighting still surpasses the mean performance of HPSV road lighting, even after excluding the error from the efficiency scores. Also, the confidence intervals derived by the bootstrapping of technical efficiency estimates indicate that significant difference between HPSV and LED road lighting. This study has proven that the performance of LED is exceptionally better than HPSV, making it a suitable candidate to substitute for HPSV as the road lighting technology.